Epithelial myoepithelial carcinoma of minor salivary gland – A case report. Issue 6 (November 2016) - Mahato, Basudev; Mandal, Samir; Deb, Tushar; Ray, Jay Gopal; Chaudhuri, Keya
Abstract: Epithelial myoepithelial carcinoma (EMC) is a rare low-grade biphasic tumour of salivary gland. Most common site of origin is the parotid gland with female predominance. We present a case of a 51-year-old male patient with symptomless slow-growing 2-year-old lump on the floor of the mouth. Histopathological diagnosis is corroborative with tubular variant of epithelial myoepithelial carcinoma. The floor of the mouth is the rare site for this tumour. In this literature, we intend to discuss the clinical and pathological aspect of EMC located on the floor of the mouth.